Glasses for D. W. - Brown, Marc (New York : Random House, 1996)
Arthur's little sister want to wear glasses like her brother and tries to prove she needs them.
Keywords: Eyeglasses -- Fiction; Anteaters -- Fiction; Brothers and sisters -- Fiction